Sinergitas Program Matoanisasi Pada Masyarakat Desa Gunting Melalui Participatory Rural Appraisal (PRA) - Aslikhah (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
To Sukorejo The City of Matoa, Sukorejo subdistrict always distributes Matoa tree seedlings from year to year, which is spread in 19 villages, one of which is the Scissors village which is the first ring in spreading Matoa tree seedlings. However, Gunting villagers still do not know more about the types or benefits of these Matoa trees and fruits. This program takes the theme of entrepreneurship which will be implemented in Gunting village of Sukorejo Sub-district of Pasuruan Regency using the Participatory Rural Appraisal (PRA) method. The purpose of this program is to increase the understanding of Gunting village community on the use of Matoa trees and fruits so that they have high economic value. The results of this program are the community ranging from adults to children more familiar with Matoa fruit and Matoa trees, as well as variants of products from processed Matoa fruit. In addition to these results, this assistance also resulted in an attractive way of packaging products, as well as an understanding of the procedures for obtaining products that have SNI standards